A New Direction: Our War Against AIDS
Filmed in southern Sudan, this film is intended to help the emerging Southern Sudan people to understand that there are new challenges following the peace accord. HIV/AIDS has spread with the movement of people into different areas and the disruption of traditional life. Using the local custom of community palaver around a fire, this film identifies key risk factors for HIV/AIDS in southern Sudan. It is produced for the Sudan Christian Aids Network of South Sudan. PAL
Paid